(untitled) (Amsterdam, 2005)
The Visualization Handbook provides an overview of the field of visualization by presenting the basic concepts, providing a snapshot of current visualization software systems, and examining research topics that are advancing the field. This text is intended for a broad audience, including not only the visualization expert seeking advanced methods to solve a particular problem, but also the novice looking for general background information on visualization topics. The largest collection of state-of-the-art visualization research yet gathered in a single volume, this book includes articles by a "who's who" of international scientific visualization researchers covering every aspect of the discipline, including: · Virtual environments for visualization · Basic visualization algorithms · Large-scale data visualization · Scalar data isosurface methods · Visualization software and frameworks · Scalar data volume rendering
Keywords: Information visualization,Thông tin ảo